Impact of Preoperative Platelet Count on Bleeding Risk and Allogeneic Transfusion in Multilevel Spine Surgery. Issue 1 (1st January 2021) - Chow, Jonathan H.; Chancer, Zackary; Mazzeffi, Michael A.; McNeil, John S.; Sokolow, Michael J.; Gaines, Tyler M.; Reif, Michaella M.; Trinh, Anthony T.; Wellington, Ian J.; Camacho, Jael E.; Bruckner, Jacob J.; Tanaka, Kenichi A.; et al.
Abstract : Study Design: This was an observational cohort study of patients receiving multilevel thoracic and lumbar spine surgery. Objective: The aim of this study was to identify which patients are at high risk for allogeneic transfusion which may allow for better preoperative planning and employment of specific blood management strategies. Summary of Background Data: Multilevel posterior spine surgery is associated with a significant risk for major blood loss, and allogeneic blood transfusion is common in spine surgery. Methods: A univariate logistic regression model was used to identify variables that were significantly associated with intraoperative allogeneic transfusion. A multivariate forward stepwise logistic regression model was then used to measure the adjusted association of these variables with intraoperative transfusion. Results: Multilevel thoracic and lumbar spine surgery was performed in 921 patients. When stratifying patients by preoperative platelet count, patients with pre-operative thrombocytopenia and severe thrombocytopenia had a significantly higher rate of transfusion than those who were not thrombocytopenic. Furthermore, those with severe thrombocytopenia had a higher rate of red blood cells, fresh frozen plasma, and platelet transfusion than those with higher platelet counts. Multivariate logistic regression found that preoperative platelet count was the most significant contributor to transfusion, with a platelet count ⩽100 having an adjusted odds ratio (OR) of transfusion of 4.88 (95% confidence interval [CI] 1.58–15.02, P  = 0.006). Similarly, a platelet count between 101and 150 also doubled the risk of transfusion with an adjusted OR of 2.02 (95% CI 1.01–4.04, P  = 0.047). The American Society of Anesthesiologists classification score increased the OR of transfusion by 2.5 times (OR = 2.52, 95% CI 1.54–4.13), whereas preoperative prothrombin time and age minimally increased the risk. Conclusion: Preoperative thrombocytopenia significantly contributes to intraoperative transfusion in multilevel thoracic lumbar spine surgery. Identifying factors that may increase the risk for transfusion could be of great benefit in better preoperative counseling of patients and in reducing overall cost and postoperative complications by implementing strategies and techniques to reduce blood loss and blood transfusions. Level of Evidence: 2 Abstract : Multilevel posterior spine surgery is associated with a significant risk for major blood loss, and allogeneic blood transfusion is common in spine surgery. Thrombocytopenia and severe thrombocytopenia results in a 2.0- and 4.9-time increase, respectively, in the risk of intraoperative transfusion during multilevel thoracic lumbar spine surgery.